Determination of the Installation Efficiency of Vertical Stationary Photovoltaic Modules with a Double-Sided “East–West”-Oriented Solar Panel - Gennadii Golub; Egidijus Blažauskas; Nataliya Tsyvenkova; Egidijus Šarauskis; Algirdas Jasinskas; Savelii Kukharets; Volodymyr Nadykto; Anna Holubenko (Applied Sciences)
The objects of this research are double-sided stationary vertical photovoltaic modules (PV-modules) with an “East–West”-oriented solar panel. The tilt angles of the Sun’s rays on PV-modules at a latitude of 50° were determined, and the installation efficiencies of both double-sided stationary vertical PV-modules with an “East–West” oriented panel and PV-modules installed at an angle of latitude with a “South” oriented panel were compared. The horizontal azimuth of the fall of the Sun’s rays during the day when using PV-modules with an “East–West”-oriented panel reaches a minimum at noon. The vertical azimuth of the Sun’s rays remains constant throughout the day and can vary from 66.55° to 113.45°. The weighted average daily installation efficiency of PV-modules with an “East–West”-oriented panel has the same value as that of PV-modules with a “South”-oriented panel, and can vary between 45.87 and 50% on different days. However, these installation options have a “mirror” value of the cosines of the Sun’s rays falling on the surface of the PV-modules and can have values from 0.917 to 1. The results can be used as a basis for evaluating the efficiency of double-sided vertical stationary solar PV-modules with an “East–West”-oriented panel.